4QInstruction. - Wold, Benjamin. (Studies on the Texts of the Desert of Judah, 2018)
In 4QInstruction: Divisions and Hierarchies , Benjamin Wold challenges the interpretation of 4QInstruction as a deterministic and dualistic composition. In a re-examination of key fragments he offers new reconstructions and translations that indicate 4QInstruction envisaged wisdom available to all humanity, divisions among humankind and communities as the result of individual adherence to wisdom, and a hierarchy of authority as a result of individual merit.